Induction of mutation in Neurospora Crassa using neem (Azadirachta Indica A. Juss) leaf extract (Dhaka University Journal of Biological Sciences, 2024)
Filamentous fungus has been used as a significant source of biotechnological applications. Neurospora crassa, a type of red bread mold, has been well recognized as a model system in fundamental scientific investigations. It can be effectively utilized as a valuable resource for molecular tools, and many mutations are available. Furthermore, N. crassa exhibits rapid growth and has no harmful properties. These characteristics indicate a significant, although unexplored, capacity of this fungus for use in biotechnological endeavors. The present investigation aimed to induce morphological changes in the N. crassa wild type by employing leaf extracts derived from Azadirachta indica A. Juss. To determine the mutagenic and growth-inhibitory effects of A. indica leaves, morphological mutants were identified and individually examined. Six morphological mutants such as albino (al), cauliflower (clf), conidial band (co.band), ropy light (ro.lig), dirty (dir), and ropy (ro) were obtained from the conidia of the wild-type N. crassa Ema (5297) strain, treated with A. indica A. Juss. leaf extracts. These mutants were compared to the wild-type, natural form of the organism in terms of their morphology, radial growth, and reproduction ability. Apparent variations were observed when a comparative study of Ema and the selected morphological mutants was undertaken. Linkage among the selected mutants in their specific linkage group was determined. Ropy, dirty, and albino were all linked to leu-3 (linkage group I), conidial-band and ropy light to trp-1 (linkage group III), and cauliflower to trp-4 (linkage group VII). Complementation was not observed in similar morphological N. crassa mutants.Dhaka Univ. J. Biol. Sci. 33(1): 79-98, 2024 (January)